2022
DOI: 10.1097/cu9.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Aquablation in men with benign prostate hyperplasia: A systematic review and meta-analysis

Abstract: Objective: The aim of the study is to investigate improvements in lower urinary tract symptoms in men with benign prostatic hyperplasia (BPH) treated with prostatic Aquablation. Materials and methods: We performed a literature search of clinical trials using the MEDLINE, Embase, and Cochrane Library databases and retrieved published works on Aquablation for the treatment of BPH up to August 2021. Unpublished works, case reports, conference proceedings, editorial comments, and letters were excluded. Risk of bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Aquablation of the prostate for men with moderate-to-severe LUTS attributable to BPH is safe and effective. The outcomes are consistently reproducible across studies, and a recent systematic review and meta-analysis has shown that the mean IPSS decreases by 16.47 points and that Qmax improves by 10.95 mL/s 19 . Aquablation is at least as good as (if not superior to) TURP at improving LUTS, QoL, and objective urodynamic parameters.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Aquablation of the prostate for men with moderate-to-severe LUTS attributable to BPH is safe and effective. The outcomes are consistently reproducible across studies, and a recent systematic review and meta-analysis has shown that the mean IPSS decreases by 16.47 points and that Qmax improves by 10.95 mL/s 19 . Aquablation is at least as good as (if not superior to) TURP at improving LUTS, QoL, and objective urodynamic parameters.…”
Section: Discussionmentioning
confidence: 81%
“…However, some outcomes exhibited large statistical heterogeneity or publication bias. In summary, aquablation appears to improve LUTS in men with BPH while preserving sexual function, but further research is necessary to validate these preliminary findings 19 .…”
Section: The Pioneering Studies: Water Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…A further study investigated the role of aquablation in larger prostates (80-150 mL) in 101 men, with significant improvements in IPSS, QoL, Qmax and PVR that was sustained for 3 years with a 3% rate of repeat surgery for LUTS [79]. A recent systematic review corroborates the findings that both IPSS and Q max are significantly improved from baseline following aquablation up to one year whilst appearing to preserve sexual function at 3 months, although the meta-analysis was limited by the extent of the heterogeneity between studies [80]. Post-operative bleeding necessitating a return to theatre or blood transfusion have been reported with Bach et al reporting a 7.9% rate of return to theatre for haemostasis, a 2 g/dL drop in haemoglobin level prior to discharge and a 2.7% transfusion rate [81].…”
Section: Aquablationmentioning
confidence: 82%
“…Optilume BPH likewise preserves sexual function with no significant impact on erectile or ejaculatory function. Recent advancements in MIST technologies include Aquablation achieving a −16.475 IPSS at 3 months with sustained results ( 7 ). Similarly, robotically assisted simple prostatectomy has also been demonstrated as an emerging modality in comparison with other simple prostatectomies or endoscopic enucleation techniques ( 8 ).…”
Section: Expert Opinionmentioning
confidence: 99%